On the performance of ldpc-coded massive mimo schemes with power-ordered noma techniques - da Silva, Mário Marques (2022)
Funding Information: Funding: This work is funded by FCT/MCTES through national funds and, when applicable, co-funded EU funds under the project UIDB/EEA/50008/2020. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.